Are s.IL33 and sST2 related to the clinical and musculoskeletal ultrasound findings of systemic sclerosis arthropathy? - Omnia Ali Abubakr; Amal Ibrahim Ahmed Othman; Rasha Mahmoud Mohamed Hammoda; Doaa Mostafa Awad ELzoghby; Nermin Hassan Abdelsalam EL-Gharbawy (Egyptian Rheumatology and Rehabilitation)
Abstract Background Systemic sclerosis (SSc) is a persistent autoimmune connective tissue disease marked by fibrosis that impacts the skin and internal organs. Serum interleukin-33 (s.IL-33) is a recently discovered cytokine expressed in various cell types, which includes fibroblasts. Inflammation and damage to tissues trigger the release, which controls the inflammatory response by blocking the suppression of tumorigenicity 2 (ST2) receptor. The present research study aims to assess the correlation among s.IL-33, soluble suppression of tumorigenicity 2 (sST2), musculoskeletal ultrasonography results, and clinical data in individuals with SSc. This case–control research comprised 30 individuals with SSc and 15 healthy controls from the rheumatology and radiology departments. Patients with SSc were categorized according to skin involvement into two groups: group A, comprising those with diffuse cutaneous SSc (dcSSc), and group B, consisting of individuals with limited cutaneous SSc (lcSSc). High-resolution musculoskeletal ultrasonography of the hands and wrists was performed, and serum levels of s.IL-33 and sST2 were measured. Results SSc patients exhibited significantly elevated levels of s.IL-33 and sST2 in comparison to healthy controls (p < 0.001). Patients in Group A demonstrated significantly elevated levels of s.IL-33 and sST2 in comparison to Group B (p < 0.001 and p = 0.004, respectively). Group A also exhibited significantly higher numbers of tender and swollen joints, as well as greater finger-to-palm distances (p < 0.001), compared to Group B. Additionally, tenosynovitis and tendon friction rub (TFR) were more prevalent in Group A (p = 0.052 and p < 0.001, respectively). s.IL-33 levels showed a positive relation with TFR, and positive correlation with the number of tender joints, swollen joints, ESR, CRP, and the US10 SSc index (p < 0.001). In a comparable pattern, sST2 levels exhibited a positive correlation with the US10 SSc index (p = 0.049). Multivariate research revealed that the number of tender joints, swollen joints, and the US10 SSc score are significant independent predictors of s.IL-33 levels in SSc patients. Conclusion Our research results highlight the significance of the s.IL-33/ST2 pathway in the pathogenicity of arthropathy associated with SSc.